2014
DOI: 10.1093/mnras/stu1363
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution study of complex organic molecules in hot cores

Abstract: We present the results of a line identification analysis using data from the IRAM Plateau de Bure Inferferometer, focusing on six massive star-forming hot cores: G31.41+0.31, G29.96-0.02, G19.61-0.23, G10.62-0.38, G24.78+0.08A1 and G24.78+0.08A2. We identify several transitions of vibrationally excited methyl formate (HCOOCH 3 ) for the first time in these objects as well as transitions of other complex molecules, including ethyl cyanide (C 2 H 5 CN), and isocyanic acid (HNCO). We also postulate a detection of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 84 publications
2
33
0
Order By: Relevance
“…It possesses a rotation toroid (Beltrán et al 2005) and gas infall accompanied by outflows (Cesaroni et al 2003;Beltrán et al 2006Beltrán et al , 2011 were used as kinematic tracers. Molecular lines from CH 3 OH, CH 3 OD, CH 3 CN, HCOOCH 3 , and C 2 H 5 CN were also reported in other surveys in the centimeter and millimeter bands (Purcell et al 2006;Vig et al 2008;Ratajczak et al 2011;Calcutt et al 2014;Favre et al 2014). Bisschop et al (2007) reported the detection of H 2 CO, CH 3 OH, C 2 H 5 OH, NH 2 CHO, CH 3 CN, C 2 H 5 CN, HCOOCH 3 , CH 3 OCH 3 , H 2 CCO, CH 3 CCH, and trans-HCOOH.…”
Section: Gal2478+008supporting
confidence: 70%
See 2 more Smart Citations
“…It possesses a rotation toroid (Beltrán et al 2005) and gas infall accompanied by outflows (Cesaroni et al 2003;Beltrán et al 2006Beltrán et al , 2011 were used as kinematic tracers. Molecular lines from CH 3 OH, CH 3 OD, CH 3 CN, HCOOCH 3 , and C 2 H 5 CN were also reported in other surveys in the centimeter and millimeter bands (Purcell et al 2006;Vig et al 2008;Ratajczak et al 2011;Calcutt et al 2014;Favre et al 2014). Bisschop et al (2007) reported the detection of H 2 CO, CH 3 OH, C 2 H 5 OH, NH 2 CHO, CH 3 CN, C 2 H 5 CN, HCOOCH 3 , CH 3 OCH 3 , H 2 CCO, CH 3 CCH, and trans-HCOOH.…”
Section: Gal2478+008supporting
confidence: 70%
“…The rotational temperature of these molecules ranges from 39 to 261K. Specifically, glycolaldehyde (CH 2 OHCHO) was reported as a detection in this source (Beltrán et al 2005;Calcutt et al 2014).…”
Section: Gal2478+008mentioning
confidence: 88%
See 1 more Smart Citation
“…Since its first detection toward the Galactic Center (Hollis et al 2000; see also Hollis et al 2001;Hollis et al 2004;Halfen et al 2006;Requena-Torres et al 2008) it has been detected in a number of other places in the ISM, both associated with formation of stars of high (Beltrán et al 2009;Calcutt et al 2014), intermediate (Fuente et al 2014) and low mass (Jørgensen et al 2012;Coutens et al 2015;Taquet et al 2015). Recently, glycolaldehyde has also been detected in comet C/2014 Q2 (Lovejoy) (Biver et al 2015).…”
Section: Glycolaldehyde Ethylene Glycol and Acetic Acidmentioning
confidence: 97%
“…with the technological advances of telescope arrays (Coutens et al 2015;Calcutt et al 2014;Biver et al 2014;Jørgensen et al 2012;Beltrán et al 2009;Cernicharo et al 2012;Bacmann et al 2016). It was originally assumed they were primarily formed as a result of gas phase chemistry.…”
Section: Introductionmentioning
confidence: 99%